2009
DOI: 10.1161/atvbaha.108.180653
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Adipose Tissue Determined by Dual Source CT Is a Risk Factor for Coronary Atherosclerosis

Abstract: Objectives-Pericardial fat as a visceral fat depot may be involved in the pathogenesis of coronary atherosclerosis. To gain evidence for that concept we sought to investigate the relation of pericardial fat volumes to risk factors, serum adiponectin levels, inflammatory biomarkers, and the quantity and morphology of coronary atherosclerosis. PϾ0.001). No association was found between BMI and coronary atherosclerosis. PAT volumes Ͼ300 cm 3 were the strongest independent risk factor for coronary atherosclerosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
216
3
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(240 citation statements)
references
References 30 publications
17
216
3
4
Order By: Relevance
“…12,14,31,[37][38][39] However, only EF surrounds the adventitia of coronary arteries without any fibrous layer, and its embryological origin is different from that of pericardial fat. 7 Although it is difficult to differentiate these two fat depots in lean subjects, it was considered important to make this distinction in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,14,31,[37][38][39] However, only EF surrounds the adventitia of coronary arteries without any fibrous layer, and its embryological origin is different from that of pericardial fat. 7 Although it is difficult to differentiate these two fat depots in lean subjects, it was considered important to make this distinction in our study.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 It has been shown that this ectopic fat is associated with the development of atherosclerotic coronary artery disease. [8][9][10][11][12][13][14][15][16] Its anatomic location, without any barrier to the adjacent myocardium, enables local paracrine interaction between EF and the myocardium, suggesting that EF could also have a functional and mechanical role in obesity-related dilated cardiomyopathy. 17,18 Myocardial lipid deposition (that is, lipid accumulation in the myocyte cytoplasm) is also a marker of ectopic fat accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Dual-source multi-slice CT-coronary angiography CT-coronary angiography and image analyses were performed as previously described (11,12). Briefly, for the analysis of coronary plaque morphology, all reconstructed data sets were evaluated at different ECG-phases for diagnostic image quality and the optimal data set was then chosen.…”
Section: Ascertainment Of Subjectsmentioning
confidence: 99%
“…4,10 In fact, in comparison with the Framingham risk score (where smoking and type 2 diabetes mellitus only account for 1.6-and 3-fold risk of having CAD, respectively), pericardial fat volume was identified as the strongest predictor of developing CAD (odds ratio of 4.1). 30,31 In addition, a case-control study identified pericardial fat volume to be a strong predicator of myocardial ischemia in patients without CAD. 32 The question of whether such predictive capabilities can be attributed specifically to epicardial fat has been addressed by recent studies such as the Heinz Nixdorf Recall study, where epicardial fat volume was significantly associated with coronary events over the course of 8 years, even after adjusting for traditional cardiovascular risk factors.…”
Section: Pathophysiological Relevance Of Human Epicardial Fatmentioning
confidence: 99%
“…30 It has been observed in both animal and human studies that segments of coronary arteries that are covered by intramyocardial bridges instead of epicardial fat do not develop atherosclerosis. 30,47 Indeed, epicardial fat has been proposed to influence the myocardium and coronary arteries via paracrine and vasocrine mechanisms. 48 Human epicardial fat is known to be a source of various bioactive molecules including adipokines and cytokines that are altered under CAD conditions.…”
Section: Mechanisms Underlying the Pathophysiological Association Betmentioning
confidence: 99%